A study on compressive strength and water absorption in cement brick using RHA as part of sand replacement - Mohd Izuan, Abu Samah (2012)
This study is to investigate the Rice Husk Ash (RHA) as part of cement replacement in cement brick with different percentage. RHA is a waste material that produced after the rice husk has been burned in the paddy factory. By relating to this study, the RHA have the same texture and physical as normal sand. The field of studies covers crucial parameters in determining the compressive strength and water absorption ability. A total of96 RHA cement bricks with dimensions of215 mm in length, 117 mm in width, and 75 mm in depth were prepared and been divided into two group according to different type of testing. The compression test used 72 bricks while water absorption test used 24 brick. All of RHA cement brick in each of the test had four different replacements of RHA percentages. There were I 0%, 20%, 30% and 0% as the control mixture. All the samples were only cured under water curing for 7 and 28 days before testing. The water to cement ratio of 0.5 and cement: sand ratio I: 10 were applied to all of the sample mixtures. In accordance to the compressive strength testing, the 20% RHA mixture shows the highest compressive strength compared to other percentage while 0% RHA mixture shows the greatest compressive strength since it is the control sample. By according to the BS 6073-1 (1981), it requires 7 N/mm2 as a minimum compressive strength and the industry required the strength about 5 N/mm2 for the building materials to be used in structural applications. The final result indicated that all sample did not achieved the minimum compressive strength. The study finally demonstrated that cement sand ratio should be higher to get better result.